2009
DOI: 10.1093/ndt/gfp107
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease, creatinine and cognitive functioning

Abstract: Global performance and specific cognitive functions are negatively affected early in CKD. Targeted screening for cognitive deficits in kidney disease patients early in their disease course may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
174
6
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(197 citation statements)
references
References 38 publications
7
174
6
10
Order By: Relevance
“…However, this finding is in contrast to most other previous cross-sectional studies (10,11,(42)(43)(44). Our results may differ from these studies because of various population characteristics.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, this finding is in contrast to most other previous cross-sectional studies (10,11,(42)(43)(44). Our results may differ from these studies because of various population characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…Our communitybased population comprised a considerable number of young subjects with normal or moderately impaired eGFR, whereas others focused on elderly or high-risk populations (9 -11,37) and included higher numbers of people with low eGFR (10,11,42,43). Another explanation might be that most previous studies did not take albuminuria into account as a possible confounder (37,(42)(43)(44). This assumption is supported by the fact that in our study eGFR did show a significant association with cognitive function in our high-risk elderly patients, but only when not accounting for albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…These data are especially notable; several studies suggest that cognition and memory are impaired in patients with renal disease, particularly during dialysis (21)(22)(23). Other studies have demonstrated limited health care literacy, independently influenced by ethnicity and socioeconomic factors, among dialysis patients (24).…”
Section: Communicationmentioning
confidence: 99%
“…Of interest, with regard to CKD, it is the cognitive performance measures involving visual-spatial organization and scanning and tracking that appear to be the most sensitive to kidney function (Elias et al, 2009;Torres et al, 2017). Thus, it is also possible that VA is merely a marker for comorbid cardiovascular disease (CVD) rather than an independent predictor of cognitive performance.…”
Section: Introductionmentioning
confidence: 99%